2006
DOI: 10.2169/internalmedicine.45.1616
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Metastasis of Malignant Melanoma

Abstract: A 67-year-old woman was admitted to our hospital with a 3-month history of lower back pain. One year earlier, the patient was diagnosed with malignant melanoma of the right maxillary bone and underwent an operation followed by adjuvant chemotherapy. (Fig. 1) A bone marrow aspirate revealed that the marrow was infiltrated by tumors composed of nests of poorly differentiated cells. These tumor cells were large and round shaped, and the cellular outlines within clumps of tumor cells were indistinct. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Other similar morphologic findings, included basophilic cytoplasm, cytoplasmic vacuoles, and prominent mitoses. All case series patients showed expected positivity for melanoma markers, including S100, HMB45, and Melan A, which was comparable to the literature that reported immunohistochemical staining results …”
Section: Discussionsupporting
confidence: 89%
“…Other similar morphologic findings, included basophilic cytoplasm, cytoplasmic vacuoles, and prominent mitoses. All case series patients showed expected positivity for melanoma markers, including S100, HMB45, and Melan A, which was comparable to the literature that reported immunohistochemical staining results …”
Section: Discussionsupporting
confidence: 89%
“…Because making the morphological diagnosis of MUP is often difficult, approximately 10% of MUP lymph node biopsies may be misdiagnosed as anaplastic carcinoma instead of MUP (5). Importantly, most melanoma cells have melanin pigment in their cytoplasm, which is a major clue to suspect MUP; however, the diagnosis of MUP is established based on immunostaining for markers such as HMB-45, Melan-A and S-100 proteins (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Savage et al [ 3 ] studied 97 patients of malignant melanoma, of these, 5.4% had marrow involvement. Bone marrow involvement from retroperitoneal, anal, tonsillar, nasal, osseous and ocular melanoma has been described [ 18 , 24 , 25 , 28 , 29 ]. Interestingly, Spiller et al reported a case of giant congenital nevus with metastatic malignant melanoma in a child [ 27 ].…”
Section: Discussionmentioning
confidence: 99%